Pre-university students’ strategies in revising ESL writing using teachers’ written ccorrective feedback - Razali, Khairil Azwar (UPM Press, 2015)
English Language writing teachers have always corrected students’ writing, hoping that their efforts would help students to write better. Students, on the other hand, may use the teacher’s feedback to improve their writing. Teachers’ strategies in giving feedback have been researched extensively, as compared to students’ strategies in revising their writing. The objectives of this study are to find out the most common strategy used by the students, and further, to determine which strategy is considered as being the most effective. A qualitative approach was used in this study, where data were collected from the analysis of students’ opinion-based essays and retrospective interviews. The study revealed that the most common strategy used was closely follow because students believed that they needed to make sure the revised essays were error-free. The results also showed that the same strategy was considered as being successful as many of the revised WCF were error free. The results implied that even though students may successfully revise the essay, they may not necessarily understand the nature of the errors committed. It is recommended that teachers give written corrective feedback with oral feedback and this should be done while students are writing the essay, in line with Flower-Hayes Cognitive Process Theory of Writing.